Analysis of Acesulfame K Sweetener on Elementary School Student’s Snacks in South Denpasar Sub-district - I Dewa Ayu Ketut Yunantariningsih; Ni Made Ayu Suardani Singapurwa; I Wayan Sudiarta; I Nyoman Rudianta; I Putu Candra (Warmadewa University Press, 2019)
This study aims to determine the content and levels of Acesulfame K sweetener in unmarked beverages without labels prepared and sold by elementary school canteens in South Denpasar subdistrict. This research is a type of descriptive research that uses survey methods with simple random sampling techniques and experiments in the laboratory. The number of primary schools in South Denpasar District is 72 schools. The population in this study were 145 types of unmarked beverages without labels that were prepared and sold by elementary school canteens in South Denpasar District. The number of samples sampled are 110 samples from 145 existing populations. The parameters of artificial sweetener in this research were Acesulfame K which was tested by HPLC. The research data are presented in tables, graphs and analyzed descriptively. The results showed that of 110 samples containing 49 acesulfam K samples (44.55%) and acesulfam K levels all samples met the requirements in accordance with the maximum allowable limit referring to the Head of POM (National Agency of Drug and Food Control) RI Regulation Number 4 of 2014.